2019
DOI: 10.4236/ojgas.2019.91004
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Molecular Biodiverisity of Hepatitis C Infection in Congolese Diabetics

Abstract: It concerned diabetic patients followed in Brazzaville and Pointe-Noire agreeing to the study, after obtaining the opinion of the ethics committee of the research in health science. All samples collected were screened for the presence of anti HCV Ab using a rapid ALERE HCV test and the Monolisa HCV Ag-Ab ultra test for confirmation in Congo. Detection of the viral RNA was done by PCR retrotranscription and genotyping was performed according to the reverse hybridization technique in France. Data analysis was do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…Although the overall prevalence of HCV in the DRC remains unknown, a systematic review of studies conducted on various population groups estimated it to be around 2.9% 11 . The prevalence found in our study, which is 11%, is higher than the overall estimates, but similar to a similar study conducted in Congo‐Brazzaville 19 …”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Although the overall prevalence of HCV in the DRC remains unknown, a systematic review of studies conducted on various population groups estimated it to be around 2.9% 11 . The prevalence found in our study, which is 11%, is higher than the overall estimates, but similar to a similar study conducted in Congo‐Brazzaville 19 …”
Section: Discussionsupporting
confidence: 82%
“…11 The prevalence found in our study, which is 11%, is higher than the overall estimates, but similar to a similar study conducted in Congo-Brazzaville. 19 In a Chinese study conducted by Hua-Fen Chen et al, HCV prevalence was found to be three times higher in diabetic patients compared with nondiabetics, while a Turkish study by Okan et al…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Sub-Saharan Africa and Southeast Asia are regions of high HBV prevalence, with carriage ranging from 8% to 20%. In the Congo, studies estimate the prevalence of hepatitis B at around 5% -15% [2] [3] [4]. The worldwide prevalence of hepatitis B among pregnant women is between 7.2 and 10.6%, compared with 7.8% in the Congo [5] [6].…”
Section: Introductionmentioning
confidence: 99%